PERBEDAAN KADAR ZAT BESI ASI PADA IBU MENYUSUI ANEMIA DAN TIDAK ANEMIA - Fitrah Ernawati; Dyah Santi Puspitasari; Susilowati Herman (Persagi, 2007)
ABSTRACT Background: National House Hold Survey reported in 2001, that prevalence of anemia among infants 0-6 month old is 61%. Anemia among young infants presumably is caused by lack of breast milk iron since young infants got their nutrient mostly from breast milk. Objectives: The objective of the study is to assess the differences of breast milk iron concentration between anemic and non anemic of lactating mothers. Methods: The design of the study is cross-sectional. The study was done in Bogor District from April to December 2004. Samples of the study were lactating mothers who have 2-4 month old children. Results: The study found out that 34% samples had anemia. There was a significant difference (p<0.05), feritin concentration (33.24 µg/dl vs 67.86 µg/dl), and breast milk iron concentration (0.15 mg/l vs 0.28 mg/l) between anemic and non anemic samples. Conclusions: The concentration of feritin, breast milk iron of the non-anemic samples were higher than the anemic samples. [Penel Gizi Makan 2007, 30(1): 8-12] Keywords: anemia status, breast milk iron, ferritin